Conservation of seeds of Crimean endemic species Alyssum calycocarpum Rupr. (Brassicaceae) and Anthyllis biebersteiniana Popl. (Fabaceae) in liquid nitrogen (–196° C) - Arapetyan, E.R. (Український ботанічний журнал, 2013)
Preservation ex situ of the seeds of Alyssum calycocarpum Rupr. (Brassicaceae) and Anthyllis biebersteiniana Popl. (Fabaceae), species endemic to the Crimean flora, has been studied using modern cryotechnique. The seeds survived after having been exposed to ultra low temperature (–196°C) during a month.